Two simplified versions of Red-Blue Facility Location - Fernandes, Cristina; Pocai, Rafael (Anais do Encontro de Teoria da Computação (ETC), 2019)
The Red-Blue Facility Location problem is a generalization of Facility Location where clients may have two types of demands and each open facility must provide for one of the types of demands. We present preliminary results for two special cases of this problem.